Law in the Shadow of Violence: Can Law Help to Improve Doctor-Patient Trust in China? - Liebman, Benjamin L. (Columbia Journal of Asian Law, 2016)
Law in the Shadow of Violence: Can Law Help to Improve Doctor-Patient Trust in China?